Making kin and taking care: intra-active learning with time, space and matter in a Johannesburg preschool - Giorza, Theresa Magdalen (School of Education, 2019)
This research explores the lives and learning of a group of Grade R children and their human and non-human collaborators, (myself included) paying particular attention to the agency of the material environment. The learning spaces of a preschool and its neighbouring park emerge as key players in the lively thinking-with that is sparked off by our engagements with each other: people, other creatures, plants, spaces, things, energies, pasts, presents and futures. The spaces cannot be separated from their relationships with time and matter (of which we are a part), nor from the stories, habits and patterns of our engagement with them. All of these connected things, material and discursive, work in the research as lively assemblages or apparatuses that change and are changed by ongoing and unanticipated events. Photographs and video clips produce new ideas about and with the data created through the project and rather than reflecting reality, these visual forms diffract with time and space to offer the researcher and the participants new and different sensory, conceptual, affective and temporal experiences. These differences make a difference to the thinking that emerges. Relationships of accountability and belonging are recognized as central concepts in the learning with the park and the preschool. Paying attention to the choices we can make about taking care of our human and nonhuman relations or 'kin’ invites new thoughts about what it means to learn together in an inner-city preschool. Learning together requires a posthuman ethics that pays attention to what matters in the entanglements of learning and the becoming response-able to one another.